Using Near Infrared Spectroscopy for Tissue Oxygenation Monitoring During Procedural Sedation: The Occurrence of Peripheral Tissue Oxygenation Changes With Respiratory Depression and Supportive Airway Measures. (31st December 2015) - O'Brien‐Lambert, Alex; Driver, Brian; Moore, Johanna C.; Schick, Alexandra; Miner, James R.
Abstract: Objectives: The objective was to assess whether respiratory depression and supportive airway measures occurring during procedural sedation are associated with changes in peripheral tissue oxygen saturation (StO2 ). Methods: This was a prospective observational study of adult patients undergoing procedural sedation in the emergency department (ED). Patients undergoing sedation with propofol, 1:1 propofol and ketamine, and 4:1 propofol and ketamine were included. Clinical interventions, sedative medication doses, vital signs, end‐tidal capnography (ETCO2 ), pulse oximetry (SpO2 ), and peripheral tissue oxygen saturation (StO2 ) were recorded. Respiratory depression was defined as the occurrence of a recorded SpO2  < 92%, an increase in ETCO2  > 10 mm Hg from baseline, or loss of capnography waveform. Supportive airway measures documented during the procedure included bag‐valve mask ventilation, airway repositioning maneuvers, increase in supplemental oxygen, and stimulation to induce respiration. Relative changes in StO2 between baseline and nadir were compared among patients who met respiratory depression criteria or required a supportive airway measure and those who did not. Results: Ninety‐three patients were enrolled. Thirty‐two patients (34.4%) met criteria for respiratory depression, and 31 (33.3%) required intervention in the form of a supportive airway measure. The median percent change in StO2 from procedure baseline to nadir in patients meeting criteria for respiratory depression was 13.6%, compared to 4.2% in those who did not. The change in StO2 in patients who required a supportive airway measure was 12.5% versus 5.4% in those who did not. Conclusions: Patients with respiratory depression and the use of supportive airway measures had greater changes in StO2 during procedural sedation than in patients who did not. Peripheral tissue oxygen saturation monitoring may be a useful tool for assessing respiratory adverse events in patients undergoing procedural sedation in the ED.